Experimentelle Untersuchung der Tropfenkondensation am chemisch modifizierten Edelstahl‐Drallrohr - Dai, Daokun; Kenig, Eugeny Y.; Numrich, Reiner (Chemie Ingenieur Technik)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Experimental Characterization of 3D Printed Structured Metal Packing with an Enclosed Column Wall - Riese, Julia; Reitze, Arnulf; Grünewald, Marcus (Chemie Ingenieur Technik)
Abstract Additive manufacturing is a promising tool for tailored solutions in chemical engineering. This applies in particular to the design of lab‐scale packed bed columns. We present experimental results to characterize a lab‐scale 3D printed structured metal packing and compare it to a conventional counterpart. The results indicate that necessary adjustments for the manufacturing process of the metal material have an influence on important operating parameters, resulting in higher specific pressure drop, slightly higher liquid holdup and lower mass transfer efficiency.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Experimentelle Untersuchungen zum Tropfenmitriss im Feedeinleitbereich von Destillationskolonnen - Fasel, Henrik; Darvishsefat, Novin; Riese, Julia; Grünewald, Marcus (Chemie Ingenieur Technik)
Abstract Im Rahmen dieses Beitrags werden experimentelle Untersuchungen zur Tropfenabscheidung im Einleitbereich eines Stoffaustauschapparates für zweiphasige Strömungen vorgestellt. Dafür wurde in einem Versuchsstand im Pilotmaßstab der qualitative Tropfenmitriss für unterschiedliche Tropfenabscheider eines Stoffaustauschapparates vermessen. Die daraus resultierenden Ergebnisse werden in diesem Beitrag hinsichtlich ihrer Aussagekraft zur Vermeidung von Tropfenmitriss diskutiert und bewertet. Darüber hinaus wird ein kurzer Ausblick über simulative Arbeiten zur Bestimmung des Tropfenmitriss gegeben.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Recent Advances in Experimental Techniques for Flow and Mass Transfer Analyses in Thermal Separation Systems - Hampel, Uwe; Schubert, Markus; Döß, Alexander; Sohr, Johanna; Vishwakarma, Vineet; Repke, Jens‐Uwe; Gerke, Sören J.; Leuner, Hannes; Rädle, Matthias; Kapoustina, Viktoria; Schmitt, Lucas; Grünewald, Marcus; et al. (Chemie Ingenieur Technik)

Dynamische Simulation von industriellen Kreislaufprozessen zur Vermeidung von Notfallsituationen bei der chemischen Absorption - Bothe, Mike; Fedorov, A.; Frei, H.; Lutters, N.; Kenig, E. Y. (Chemie Ingenieur Technik)

Numerische Simulation von Gravidestillationsapparaten zur Trennung eines binären Ethanol/Wasser‐Gemisches - Wende, Marc; Philippi, K.; Kenig, Eugeny (Chemie Ingenieur Technik)

Untersuchung des dynamischen Prozessverhaltens bei Betriebsstörungen im Bereich der chemischen Absorption - Bothe, Mike; Fedorov, Alexander; Frei, Herrmann; Lutters, Nicole; Kenig, Eugeny Y. (Chemie Ingenieur Technik)

Entwicklung von Echtzeitmodellen für Kreislaufprozesse der chemischen Absorption - Fedorov, Alexander; Frei, Herrmann; Bothe, Mike; Lutters, Nicole; Kenig, Eugeny Y. (Chemie Ingenieur Technik)

Separation Units 4.0 – Trennapparate heute und morgen - Riese, Julia; Hoff, Andreas; Stock, Jürgen; Górak, Andrzej; Grünewald, Marcus (Chemie Ingenieur Technik)
Abstract Die chemische Industrie sieht sich mit gravierenden Herausforderungen konfrontiert: Die Einhaltung der Klimaschutzziele, die Auswirkungen der Energiewende und die zunehmende Bedeutung der Kreislaufwirtschaft treffen die gesamte Wertschöpfungskette. Lösungsansätze von der Prozess‐ über die Apparateebene bis hin zum Einzelphänomen sind notwendig, um die Wettbewerbsfähigkeit dieses zentralen Industriezweigs zu erhalten. In diesem Beitrag werden aktuelle Entwicklungen und zukünftige Handlungsfelder in der Trenntechnik, die für diese Herausforderungen wertvolle Beiträge leisten können, dargestellt.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Modular Production with Bio‐Based Resources in a Decentral Production Network - Finkbeiner, Marco; Pannok, Maik; Fasel, Henrik; Riese, Julia; Lier, Stefan (Chemie Ingenieur Technik)
Abstract The change in process industry from fossil resources to alternative feedstock is indispensable due to the scarcity of resources and global warming. This leads to new challenges for the production systems. On the market side, rapid innovation is accompanied by shorter product life cycles leading to an increasing uncertainty of demand in terms of product type, volume and location. Therefore, the following five elements are combined into a concept to address these challenges: transformable production systems, local bio‐based resources, CO 2 as feedstock, renewable energy and decentral production network with local economies.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry